Penerapan Community Based Tourism (CBT) Dalam Upaya Pengembangan Pariwisata di Tangkahan Kabupaten Langkat - Nurhafizhah Khairi (Politeknik Pariwisata Medan, 2022)
Tangkahan is a tourist attraction that moves on the potential of ecotourism with good community involvement. The concept of CBT (Community Based Tourism) is applied to realize the management of tourism by involving local communities, forming institutional tangkahan tourist attraction and community business groups. Stakeholders involved in the management of tourist attractions consist of community groups, government and private organizations that have their respective roles in realizing tangkahan Tourism Development. This study uses qualitative research that uses a community-based research model as a community effort to provide support, strength, resources, and participation in the research process to create informative research products. Data sources in this study are primary and secondary data sources with observation data collection techniques, interviews and documentation, data analysis using data collection stages, data condensation, data presentation and conclusion. The results showed that tangkahan tourism development comes from the initiative of local communities who have a common understanding that the village has a growing tourism potential. The creation of the tangkahan ecowosata development program and the emergence of community businesses as a form of tangkahan tourism development results. Based on the findings of researchers Tangkahan Tourism Institute managed to build community kelolmpok coordinated in writing and cooperate with the private sector and the Institute of Mount Lauser National Park with the same synergy to keep and menjadikawan Tangkahan area awake and attract more tourists. Keywords: tourism, Community Based Tourism (CBT), community